Faktor-Faktor Yang Mempengaruhi Kesehatan Mental Pada Remaja Sekolah Menengah Pertama (SMP) Swasta “X” Di Wilayah Uptd Puskesmas Melayu Kota Piring - Evike Astriyani; Ennimay Ennimay; Rizki Sari Utami Muchtar (Jurnal Mahasiswa Ilmu Kesehatan, 2025)
The issue of mental health has been widely discussed in recent years. In general, mental health is the state of an individual who is aware of their own ability to cope with the normal stresses of life, therefore mental health is very important, especially among teenagers, because during adolescence there are many changes. psychosocial such as cognitive, psychological, social and biological. This development is a crisis event for teenagers which can cause impacts such as anxiety, stress and depression. The aim of this research is to determine the factors that influence mental health in teenagers at private junior high school (SMP) "X" in the working area of ​​the UPTD Puskesmas Melayu, Piring City. Cross sectional research method. The sample used was 35 respondents with a total sampling technique. Data was processed using the Chi square test. Based on univariate analysis, it was found that most of the family support was 23 respondents (65.7%), the community environment was low for 22 respondents (62.9%), peers were not good for 27 respondents (48.6%), the school environment was good for 20 respondents. (57.1%) and high mental health of 22 respondents (62.9%). It is hoped that the research conclusions can be used as a reference for preventing mental health disorders so that they do not have a negative impact on the future of adolescents.